Provably secure private key protection scheme for smart mobile terminal - Jun MA; Jian-feng MA; Yuan-bo GUO (Tongxin xuebao)
A provable security scheme for private key protection of smart mobile terminal (SMT) was presented.In the scheme a improved security mechanism is incorporated,which includes password protection,key division and partial key retrieval from server of strong computing capability in order to protect private key security.Compared with previous proposals,the scheme has the following advantages.It reduces computation amount and storage of SMT,and simplifies parameter setting for interaction processes.It takes time synchronization between SMT and server into account.The latter characteristic not only provides better protection of scheme from replay attacks,but also offers a highly efficient mechanism of user private key disabling,and avoiding complex operation of user and extra storage of other device.The investigation has indicated that improved private key protection to SMT can be well achieved with this scheme.The scheme has also been proved to provide satisfactory security in the random oracle model.